Growth Response and Feed Conversion Efficiency of Tor putitora (Ham.) Fry at Varying Dietary Protein Levels - Sawhney, Simple; Gandotra, Roopma (Pakistan Journal of Nutrition, 2009)
The aim of this work was to study the effect of different dietary protein levels Viz. 30, 35, 40, 45 and 50% on growth and Feed Conversion Efficiency (FCE) of Tor putitora fry. Five iso-caloric diets containing different levels of protein such as 30, 35, 40, 45 and 50% were prepared in pellet form and fed to Tor putitora fry for a period of 120 days to determine the optimum protein requirement in laboratory conditions. Specific growth rates were 0.719, 0.696, 0.538, 0.486 and 0.364 in 45, 50, 40, 35 and 30% protein diet respectively. Food conversion efficiency was minimum at 30% (7.62), it further increased with increasing protein levels up to 45% (14.46) but beyond this it again decreases i.e. at 50% (13.85). On the basis of weight gain the following trend emerges 45%>50%>40%>35%>30%. The results confirm the best protein level for optimum growth of Tor putitora seems to be 45% and it is not significantly different from that achieved by 50% (p